The influence of age and growth rate of female Baltic salmon upon the offspring at the artificial reproduction - Peslak, Ya.K. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1968)
The results of investigations on the influence of the qualities of parent fish of the Baltic salmon (Salmo salar) on the quality of the fry reared in fish hatcheries in Latvia in 1964-1966 are described. In October 1964 and 1965, 24 versions of cross-fertilizations between different pairs of parent fish were performed. The results of the crossings are presented. The influence of the growth rate of the female salmon in the period of its marine life upon the weight of the young-of-the-year salmon is described. Data on the chemical composition and on the nutrient content of eggs of different size as well as on the length and weight of the larvae in dependence of the egg size are considered. For the selection of parent fish for artificial reproduction the egg size and the optimum combination of the pairs of parent fish should be accounted for. Published Not Known